CHILD DEVELOPMENT CENTERS’ PROFILE AND COMPLIANCE TO QUALITY STANDARDS: INPUT FOR MUNICIPAL ORDINANCE - Sibal - Tumbali, Norma (International Journal of Arts, Sciences and Education, 2023)
ABSTRACT Using the descriptive research design, this study investigated the profile of the Child Development Centers (CDCs), their level of compliance to standards set by the Department of Social Welfare and Development (DSWD) as well as the enabling and restraining factors in their operations and management. The respondents were the 26 CDC teachers in Peñablanca, Cagayan with focus group discussion participants coming from the employees/officers of the municipal and regional levels of the DSWD. Results showed that the CDCs of Peñablanca are compliant to the standards despite their meager budget. The success of CDCs in Peñablanca is attributed to the dedication of teachers, strong support from parents, barangay officials, and the community, and effective monitoring and evaluation by social work and development offices. On the other hand, challenges such as limited budget allocation, insufficient modern instructional materials, outdated facilities and equipment, and the absence of permanent teaching positions hinder the optimal functioning and growth of these centers. All of these challenges may be resolved by enacting the municipal ordinance proposed for the enhancement of the CDCs.